Vital Signs: Cervical Cancer Incidence, Mortality, and Screening — United States, 2007–2012 - Benard, Vicki B. (MMWR Morb Mortal Wkly Rep, 2014)
BACKGROUND: Cervical cancer screening is one of the greatest cancer prevention achievements, yet some women still develop or die from this disease. OBJECTIVE: To assess recent trends in cervical cancer incidence and mortality, current screening percentages, and factors associated with higher incidence and death rates and inadequate screening. METHODS: Percentages of women who had not been screened for cervical cancer in the past 5 years were estimated using data from the 2012 Behavioral Risk Factor Surveillance System survey. State-specific cervical cancer incidence data from the United States Cancer Statistics and mortality data from the National Vital Statistics System were used to calculate incidence and death rates for 2011 by state. Incidence and death rates and annual percentage changes from 2007 to 2011 were calculated by state and U.S. Census region. RESULTS: In 2012, the percentage of women who had not been screened for cervical cancer in the past 5 years was estimated to be 11.4%; the percentage was larger for women without health insurance (23.1%) and for those without a regular health care provider (25.5%). From 2007 to 2011, the cervical cancer incidence rate decreased by 1.9% per year while the death rate remained stable. The South had the highest incidence rate (8.5 per 100,000), death rate (2.7 per 100,000), and percentage of women who had not been screened in the past 5 years (12.3%). CONCLUSIONS: Trends in cervical cancer incidence rates have decreased slightly while death rates have been stable over the last 5 years. The proportion of inadequately screened women is higher among older women, Asians/Pacific Islanders, and American Indians/Alaska Natives. IMPLICATIONS FOR PUBLIC HEALTH PRACTICE: There continue to be women who are not screened as recommended, and women who die from this preventable cancer. Evidence-based public health approaches are available to increase women’s access to screening and timely follow-up of abnormal results.